PENGARUH STRATEGI REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING) TERHADAP KEMAMPUAN NUMERASI SISWA PADA PEMBELAJARAN MATEMATIKA - Nurani, Mughni; Irawati, Riana; Maulana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
The low numeracy skills of students serve as the background of this study. Therefore, this study aims to determine the difference between the effect of REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning strategy with conventional learning in improving students' numeracy skills in mathematics learning. This research is a quasi-experiment with nonequivalent control group design. This research instrument utilized a numeracy test. Data analysis comprised namely normality test, homogeneity test, mean difference test, and normalized Gain (N-Gain) test. The results showed that REACT learning strategy and conventional learning can improve students' numeracy skills. The REACT learning strategy demonstrated an improvement in students' numeracy skills with an N-Gain score of 0.58 and an N-Gain percentage of 57.93% in the medium and moderately effective category. Conversely, the conventional learning resulted in an N-Gain score of 0.35 and an N-Gain percentage of 35.49% with moderate and ineffective categories. Consequently, REACT learning strategy is better than conventional learning in improving students' numeracy skills.